Efficacy of a novel iPod-based navigation system compared to traditional navigation system in total knee arthroplasty. Issue 1 (1st January 2017) - Mullaji, Arun B.; Shetty, Gautam M.
Abstract: Background: This prospective study aimed to verify the efficacy of a novel, hand-held, iPod-based navigation system in comparison to traditional navigation system for total knee arthroplasty (TKA). Methods: Limb alignment, tibial and distal femoral bone cut thickness and plane were recorded intraoperatively using both iPod-based and traditional navigation system in 36 knees undergoing primary TKAs. Results: Intraoperatively, the iPod-based navigation system showed good to excellent correlation and reliability for tibial and distal femoral bone cut thickness, plane of the femoral cut and limb alignment when compared to the traditional navigation system. Conclusions: Despite its quick registration feature, the iPod-based system has an efficacy similar to traditional navigation system and is a positive step towards making navigation systems for TKA more compact, user-friendly, time and cost-effective.